Shining Light on Black Rock Coatings in Smelter-Impacted Areas - Schindler, Michael; Mantha, Nathalie; Kyser, Kurt; Murayama, Mitsuhiro; Hochella, Michael (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2012)
SUMMARY Earth scientists have long known of the existence of black coatings on exposed rocks in smelter-impacted areas such as Sudbury, Ontario or Rouyn-Noranda, Québec. Black rock coatings in the Greater Sudbury area are remarkable geological records of atmospheric conditions, including mixing, scavenging, and oxidation processes, deposition rates, and the nature and source of anthropogenic releases to the atmosphere. The coatings are composed of an amorphous silica matrix that has trapped atmosphere-borne nanoparticles and has preserved their chemical and isotopic signature. These coatings are the product of high emissions of SO2 and subsequent non-stoichiometric dissolution of exposed siliceous rocks. The coatings contain spherical smelter-derived Cu–Ni-oxide particulate matter (micrometre and nanometre-sized) and metal-sulphate-rich layers composed of nanometre aggregates of Fe–Cu sulphates. Lead, As, and Se-bearing nanoparticles emitted from smelters are incorporated in metal-sulphate-rich layers along the atmosphere-coating interface, presumably during coating formation. On a regional scale, ratios between different metal(loid)s in the coatings indicate that small diameter primary Pb, As and Se-bearing sulphate aerosols have been deposited at higher rates compared to larger, Ni-bearing particulate matter. High sulphur isotope values in coatings closer to smelting centres and their decrease with distance from the smelters is attributed to an increase in mixing of primary and secondary sulphates.